Cooling of air using heptadecane phase change material in shell and tube arrangement: Analytical and experimental study - Anisur, M.R.; Kibria, M.A.; Mahfuz, M.H.; Saidur, R.; Metselaar, I.H.S.C. (Elsevier, 2014)
A shell and tube latent heat storage (LHS) system using heptadecane with melting point 22.33 degrees C for active cooling of air has been analyzed analytically and experimentally in this paper. A theoretical model of laminar forced convection with varying wall temperature due to phase change material (PCM) outside a double wall circular tube and air as heat transfer fluid (HTF) inside a tube was employed to analyze active cooling of air. The analytical prediction in terms of outlet temperature was validated with experimental data. Furthermore, influences of some important design parameters (e.g. inner radius and thickness of the tube) on cooling effect were investigated. It was found that an optimum inner radius and thickness of the tube should be considered to design an LHS system. Better co-efficient of performance (COP) was observed for higher inlet air temperature while the outlet air temperature was almost identical. In this study, the COP of cooling was found 4.16 for 34.5 degrees C inlet air temperature using tube with 5.35 mm inner radius and 1 mm thickness. Some important thermophysical properties of heptadecane e.g. specific heat, thermal conductivity and density at liquid state were also examined and found 2.66 kJ kg(-1) K-1, 0.151 W m(-1) K-1 and 774 kg m(-3), respectively. (C) 2014 Elsevier B.V. All rights reserved.